Aberrant epileptic seizure identification: A computer vision perspective. (February 2019) - Ahmedt-Aristizabal, David; Fookes, Clinton; Denman, Simon; Nguyen, Kien; Sridharan, Sridha; Dionisio, Sasha
Highlights: First of its kind method to identify aberrant semiology during epileptic seizures. Analyse entire body simultaneously using a shallow end-to-end architecture. Extract spatio-temporal features capturing seizure motion patterns. Identify previously unseen aberrant semiology, or similar past patients. Could provide diagnostic support to clinicians, based on pre-learned semiologies. Abstract: Purpose: The recent explosion of artificial intelligence techniques in video analytics has highlighted the clinical relevance in capturing and quantifying semiology during epileptic seizures; however, we lack an automated anomaly identification system for aberrant behaviors. In this paper, we describe a novel system that is trained with known clinical manifestations from patients with mesial temporal and extra-temporal lobe epilepsy and presents aberrant semiology to physicians. Methods: We propose a simple end-to-end-architecture based on convolutional and recurrent neural networks to extract spatiotemporal representations and to create motion capture libraries from 119 seizures of 28 patients. The cosine similarity distance between a test representation and the libraries from five aberrant seizures separate to the main dataset is subsequently used to identify test seizures with unusual patterns that do not conform to known behavior. Results: Cross-validation evaluations are performed to validate the quantification of motion features and to demonstrate the robustness of the motion capture libraries for identifying epilepsy types. The system to identify unusual epileptic seizures successfully detects out of the five seizures categorized as aberrant cases. Conclusions: The proposed approach is capable of modeling clinical manifestations of known behaviors in natural clinical settings, and effectively identify aberrant seizures using a simple strategy based on motion capture libraries of spatiotemporal representations and similarities between hidden states. Detecting anomalies is essential to alert clinicians to the occurrence of unusual events, and we show how this can be achieved using pre-learned database of semiology stored in health records.